1997
DOI: 10.1074/jbc.272.11.7127
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of Type I Procollagen by Human Mast Cell Chymase Initiates Collagen Fibril Formation and Generates a Unique Carboxyl-terminal Propeptide

Abstract: The ability of human mast cell chymase and tryptase to process procollagen was examined. Purified human intestinal smooth muscle cell procollagen was incubated with human mast cell tryptase or human mast cell chymase. Purified chymase, but not tryptase, exhibited procollagen proteinase activity in the presence of EDTA. Addition of purified porcine heparin over a range of 0.1-100 g/ml did not affect either the rate or the products of procollagen chymase cleavage. The cleavage site of chymase on the pro-␣1(I) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
117
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 181 publications
(118 citation statements)
references
References 39 publications
1
117
0
Order By: Relevance
“…However, we cannot exclude MMP-independent effects of mMCP-4 on the connective tissue components. For example, we have shown previously that fibronectin is a substrate for mMCP-4 (36), and it has been shown that MC chymase can degrade type I procollagen (37). Furthermore, chymase has been reported to activate human interstitial procollagenase by cleavage of the Leu 83 -Thr 84 bond (38).…”
Section: Discussionmentioning
confidence: 99%
“…However, we cannot exclude MMP-independent effects of mMCP-4 on the connective tissue components. For example, we have shown previously that fibronectin is a substrate for mMCP-4 (36), and it has been shown that MC chymase can degrade type I procollagen (37). Furthermore, chymase has been reported to activate human interstitial procollagenase by cleavage of the Leu 83 -Thr 84 bond (38).…”
Section: Discussionmentioning
confidence: 99%
“…Heparin facilitates the processing of prochymase [10,11] and β-protryptase [12] by dipeptidylpeptidase I (DPPI, Cathepsin C), a cysteine protease. Chymase converts angiotensin I to angiotensin II [13,14], processes type I procollagen to collagen fibrils [15] and degrades various cytokines [16]. Cathepsin G is serine protease expressed by MC TC cells [17] as well as by neutrophils and monocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Chymases also can influence structural remodeling through their ability to degrade extracellular matrix proteins, including fibronectin and collagen type IV, possibly through activation of matrix metalloproteinases (MMPs) (MMP-1, MMP-3, and MMP-9) (10)(11)(12). Chymases also stimulate collagen fibirillogenesis by cleavage of type I procollagen (13).…”
mentioning
confidence: 99%